The Influence of User Interface, Payment Flexibility, Flash Sales, and Perceived Enjoyment on Switching Intention among Gojek Application Users in Bandar Lampung - Dina Sabila Darmawan; Euis Mufahamah; Hamida Nur Rahmawati (Yayasan Multidimensi Kreatif, 2026)
The increasingly fierce competition between digital service applications encourages companies to understand the factors that influence user switching intention. This study aims to analyze the influence of user interface, payment flexibility, flash sale, and perceived enjoyment on the switching intention of Gojek application users in Bandar Lampung City. This study uses a quantitative approach with a survey method through the distribution of questionnaires to 105 respondents who are active users of the Gojek application in Bandar Lampung. The data analysis techniques used include validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis. The results of the study show that partially user interface, payment flexibility, flash sale, and perceived enjoyment have a significant effect on Gojek users' switching intentions. Simultaneously, the four independent variables also have a significant effect on switching intention. These findings show that a good user experience, ease and flexibility of transactions, the right promotional strategy, and the level of enjoyment of using the app play an important role in suppressing users' intention to move to a competitor's app. This research is expected to be a consideration for Gojek in designing a more effective user retention strategy.